Systemic RNA delivery to dendritic cells exploits antiviral defence for cancer immunotherapy - Kranz, Lena M.; Diken, Mustafa; Haas, Heinrich; Kreiter, Sebastian; Loquai, Carmen; Reuter, Kerstin C.; Meng, Martin; Fritz, Daniel; Vascotto, Fulvia; Hefesha, Hossam; Grunwitz, Christian; Vormehr, Mathias; et al. (Nature (London), 2016)
The development of a nanoparticle RNA vaccine is reported that preferentially targets dendritic cells after systemic administration, and is shown to provide durable interferon-α-dependent antigen-specific immunity in mouse tumour models; initial results in advanced melanoma patients indicate potential efficacy in humans. An anti-cancer nanoparticulate RNA vaccine The systemic delivery of vaccine antigens into the dendritic or antigen-presenting cells of the immune system faces many technical challenges. This study reports the development of a nanoparticle RNA vaccine that preferentially targets dendritic cells after systemic administration. The vaccine consists of RNA-lipoplexes based on well-known lipid carriers; targeting is achieved by optimally adjusting the negative net charge of the nanoparticles, with no need for functionalization with molecular ligands. Intravenous administration produces durable type-I-interferon-dependent antigen-specific immunity in mouse tumour models. Initial results in patients with advanced melanoma indicate potential efficacy in humans. Virtually any tumour antigen can be encoded by RNA, so this approach is potentially more generally applicable in cancer immunotherapy. Lymphoid organs, in which antigen presenting cells (APCs) are in close proximity to T cells, are the ideal microenvironment for efficient priming and amplification of T-cell responses 1 . However, the systemic delivery of vaccine antigens into dendritic cells (DCs) is hampered by various technical challenges. Here we show that DCs can be targeted precisely and effectively in vivo using intravenously administered RNA-lipoplexes (RNA-LPX) based on well-known lipid carriers by optimally adjusting net charge, without the need for functionalization of particles with molecular ligands. The LPX protects RNA from extracellular ribonucleases and mediates its efficient uptake and expression of the encoded antigen by DC populations and macrophages in various lymphoid compartments. RNA-LPX triggers interferon-α (IFNα) release by plasmacytoid DCs and macrophages. Consequently, DC maturation in situ and inflammatory immune mechanisms reminiscent of those in the early systemic phase of viral infection are activated 2 . We show that RNA-LPX encoding viral or mutant neo-antigens or endogenous self-antigens induce strong effector and memory T-cell responses, and mediate potent IFNα-dependent rejection of progressive tumours. A phase I dose-escalation trial testing RNA-LPX that encode shared tumour antigens is ongoing. In the first three melanoma patients treated at a low-dose level, IFNα and strong antigen-specific T-cell responses were induced, supporting the identified mode of action and potency. As any polypeptide-based antigen can be encoded as RNA 3 , 4 , RNA-LPX represent a universally applicable vaccine class for systemic DC targeting and synchronized induction of both highly potent adaptive as well as type-I-IFN-mediated innate immune mechanisms for cancer immunotherapy.